2020
DOI: 10.1643/ci2020008
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Snailfish (Cottiformes: Liparidae) Closely Related to Careproctus melanurus of the Eastern North Pacific

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…When comparing with other species, we used the characters of type specimens from the original descriptions, since widespread snailfishes can represent themselves species complexes, as is shown for C. melanurus/C. ambustus (Orr et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…When comparing with other species, we used the characters of type specimens from the original descriptions, since widespread snailfishes can represent themselves species complexes, as is shown for C. melanurus/C. ambustus (Orr et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Our species differs from C. ambustus in a number of features. In C. ambustus, the jaw teeth are weakly three-lobed and small (form 23-45 oblique rows of 11-27 teeth each), the disc is longitudinally oval and concave, the anus opens at some distance from the disc (equal to about 1/3 of the disc length); the lower lobe of P is almost equal in length to the upper lobe (on average, 16.7 and 18.5% SL, respectively) (Orr et al, 2020. Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we observed the reproductive behavior of a deep-sea snail sh, C. pellucidus (Gilbert and Burke 1912), which is distributed in the North Paci c Ocean region at depths > 200 m, in an aquarium. Careproctus is one of the most diverse genera among the Liparidae, comprising at least 140 known species (Orr et al 2019(Orr et al , 2020. Most Careproctus species are found in the deeper zones of the sea, and new species continue to be described (Chernova 2005;Orr 2012;Chernova 2014a, b;Orr 2016;Kai and Matsuzaki 2019;Matsuzaki et al2020).…”
Section: Introductionmentioning
confidence: 99%